Hadith Approach in Handling Baby Blues Syndrome: Case Study at Madina Pratama Clinic, Medan - Poppy Radana; Nawir Yuslem (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Baby blues syndrome is a psychological problem often experienced by postpartum mothers, characterized by anxiety, mood swings, and emotional stress. From an Islamic perspective, the hadith of the Prophet Muhammad SAW offers guidance on calmness, patience, and social support that can help mothers face these emotional challenges. This study aims to explore the effectiveness of the hadith approach in overcoming baby blues syndrome using a mixed methods method, namely a combination of qualitative and quantitative approaches. Data were collected through in-depth interviews, quantitative questionnaires using the Edinburgh Postnatal Depression Scale (EPDS), and participant observation of postpartum mothers at the Madina Pratama Clinic, Medan. The results showed that mothers who had a better understanding of the hadith on calmness and patience tended to have lower levels of anxiety. In addition, worship practices such as dhikr, prayer, and reading the Qur'an play a role in improving maternal emotional well-being. However, several inhibiting factors in the application of the hadith approach include lack of access to relevant Islamic education, limited time for worship due to being busy taking care of babies, and lack of social support from the surrounding environment. This study provides insight that a hadith-based approach can be an effective method in dealing with baby blues syndrome if supported by more inclusive religious education and a strong social support system. Therefore, the integration of Islamic teachings and modern psychological approaches in postpartum maternal health services needs to be further developed to improve maternal mental well-being.